2017
DOI: 10.1111/bph.13725
|View full text |Cite
|
Sign up to set email alerts
|

5‐fluorouracil causes endothelial cell senescence: potential protective role of glucagon‐like peptide 1

Abstract: BACKGROUND AND PURPOSE5-fluorouracil (5FU) and its prodrug, capecitabine, can damage endothelial cells, whilst endothelial integrity is preserved by glucagon-like peptide 1 (GLP-1). Here, we studied the effect of 5FU on endothelial senescence and whether GLP-1 antagonizes it. EXPERIMENTAL APPROACHEA.hy926 cells were exposed to 5FU or sera from patients taking capecitabine, with or without pre-incubation with GLP-1. Senescence was identified by expression of senescence-associated β-galactosidase and p16INK4a an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…In our study, 5-FU caused HS-5 cell cycle arrest in G1 phase ( Figure 2 c,d) and a significant rise in apoptosis ( Figure 2 e,f), suggesting that apoptosis is a response for HS-5 stromal cells to 5-FU treatment the same as cancer cells respond to 5-FU. Moreover, although a very small number of documents suggest that senescence is also another cellular response to 5-FU [ 84 ], using senescence-specific SA-β-gal staining, a classical index for cellular senescence, we found an increase in positive ratio after 5-FU treatment ( Figure 2 g,h), suggesting that, apart from apoptosis, some survival HS-5 cells underwent senescence with permanent cell cycle arrest. Encouragingly, we found that ASP alleviated stress in HS-5 cell caused by 5-FU treatment.…”
Section: Resultsmentioning
confidence: 80%
“…In our study, 5-FU caused HS-5 cell cycle arrest in G1 phase ( Figure 2 c,d) and a significant rise in apoptosis ( Figure 2 e,f), suggesting that apoptosis is a response for HS-5 stromal cells to 5-FU treatment the same as cancer cells respond to 5-FU. Moreover, although a very small number of documents suggest that senescence is also another cellular response to 5-FU [ 84 ], using senescence-specific SA-β-gal staining, a classical index for cellular senescence, we found an increase in positive ratio after 5-FU treatment ( Figure 2 g,h), suggesting that, apart from apoptosis, some survival HS-5 cells underwent senescence with permanent cell cycle arrest. Encouragingly, we found that ASP alleviated stress in HS-5 cell caused by 5-FU treatment.…”
Section: Resultsmentioning
confidence: 80%
“…Silent ischemia due to cardiac stress test has been reported in 6–7% of 5-FU-treated patients (Lestuzzi et al, 2014 ). The mechanisms involved in the CTX of 5-FU and its metabolites involve inhibition of NO (Cianci et al, 2003 ; Shoemaker et al, 2004 ), enhanced generation of ROS/RNS (Lamberti et al, 2014 ), higher endothelial thrombogenicity (Kalam and Marwick, 2013 ) and senescence (Altieri et al, 2017 ), and DNA and RNA damage. 5-FU can induce oxidative stress in cardiomyocytes and endothelial cells.…”
Section: Antimetabolitesmentioning
confidence: 99%
“…Cardiotoxicity: Among all antimetabolites, 5-FU is most extensively studied drugs in term of cardiotoxicity 37 . It has a direct effect on myocardial cells and on endothelial cells 38 . Mononuclear inflammations and myocardial necrosis have been observed in a patient who died from myocardial infarction followed by 5-FU therapy 39 .…”
Section: Antimetabolite (5-florouracil (5fu) Cytarabine and Capecitamentioning
confidence: 99%